The Role of Sheikh Abdul Djalil bin Musa Rifai in the Spread of the Tarekat in Cianjur, West Java 1887 – 1942 - Dudang Abdul Karim; Wahyudin; Khoirul Ibad (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study examines the role of Sheikh Abdul Djalil bin Musa Rifai in the spread of Sufi orders (tarekat) in Cianjur, West Java, during the period 1887–1942. The research employs the historical method through literature review, manuscript analysis, and interviews with local religious figures and historians. The findings indicate that Syeikh Abdul Djalil bin Musa Rifa’i contributed significantly to the development of Sufi traditions through scholarly and spiritual networks connected to Syekh Abdul Karim al-Bantani. His teachings were associated with several mu‘tabarah Sufi orders, including Rifā‘iyyah, Syattariyyah, Sammaniyyah, Qadiriyyah, and Naqshbandiyyah. The term “Kubrawiyah” found in local manuscripts is interpreted as a local designation for a spiritual tradition rather than a new Sufi orders. The study concludes that his contribution was not limited to religious dissemination, but also extended to the formation of a cohesive and harmonious Muslim community in Cianjur. This research highlights the importance of local Sufi networks in shaping religious life and social cohesion in Indonesian Islamic history.